Spellbound - McDonald, Janet 1954-2007 (Farrar, Straus and Giroux, 2001)
Raven, a teenage mother and high school dropout living in a housing project, decides, with the help and sometime interference of her best friend Aisha, to study for a spelling bee which could lead to a college preparatory program and four-year scholarship.
Raven, a teenage mother and high school dropout living in a housing project, decides, with the help and sometime interference of her best friend Aisha, to study for a spelling bee which could lead to a college preparatory program and four-year scholarship.
Keywords: Englisch; Schwarze. USA; African Americans -- Fiction; Best friends -- Fiction; English language -- Orthography and spelling -- Fiction; English language -- Spelling -- Fiction; High school dropouts -- Fiction; Teenage mothers -- Fiction